PENGARUH GAYA HIDUP DAN KELAS SOSIAL TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE MEREK SAMSUNG DI BHINTANG PONSEL PADANG - Tia Faulina; Febsri Susanti (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2023)
This study aims to determine the Influence of Lifestyle and Social Class on Samsung Smartphone Purchase Decisions at Bhintang Ponsel Padang. The sampling method used purposive sampling technique as many as 80 samples, using analytical techniques, research instrument testing, classical assumption test, multiple linear regression and hypothesis testing. The results showed that lifestyle did not have a positive and significant effect on purchasing decisions, Social Class had a positive and significant effect on purchasing decisions and simultaneously there was a significant influence between lifestyle and social class on purchasing decisions